Assessment of the efficacy and tolerability of ruxolitinib for the treatment of myelofibrosis patients in a real‐life setting: An Italian MYNERVA Project. (27th January 2023) - Coltro, Giacomo; Sant'Antonio, Emanuela; Palumbo, Giuseppe A.; Mannelli, Francesco; De Stefano, Valerio; Ruggeri, Marco; Elli, Elena M.; Zanotti, Roberta; Borsani, Oscar; Bertozzi, Irene; Duminuco, Andrea; Betti, Silvia; et al.
Abstract: Background: Incorporating real‐world data in the drug development process allows the improvement of health outcomes by providing better representation of actual patterns of drug safety and efficacy. Aims and Methods: Here, we present the results of a retroprospective, observational real‐life study of 154 patients with myelofibrosis treated with ruxolitinib in a real‐life setting in seven Italian centers of the MYNERVA project. Results: Median drug exposure was 29 (range, 3–98) months. Discontinuation rate was 27% after a median time of 13 (range, 3–61). While hematological toxicities were in line with previous findings, infections occurred frequently, representing a not negligible cause of discontinuation and death. Anemia, symptoms, and spleen responses were obtained at any time in 23%, 91%, and 68% of patients, respectively; most patients achieved their responses by week 24. Larger splenomegaly and delayed treatment initiation correlated with lower spleen response at 24 weeks. Spleen response was associated with a superior overall survival, regardless of DIPSS. Of interest, both achievement and loss of spleen response had prognostic implications. Discussion and Conclusion: Overall, our findings provide insights on the efficacy and safety of ruxolitinib in a real‐world, multicenter cohort of Italian MF patients. Abstract : This Brief Report presents the results of a real‐world study from the MYNERVA project that enrolled 154 patients with myelofibrosis treated with ruxolitinib. Hematological toxicities were consistent with previous studies, while infections occurred frequently, representing a not negligible cause of discontinuation and death. Anemia, symptoms and spleen responses were obtained by 23%, 91%, and 68% of patients, respectively. Both achievement and loss of spleen response had prognostic implications.